Does unemployment insurance offer incentives to take jobs in the formal sector? - Mariano Bosch (IZA World of Labor, 2016)
Unemployment insurance can be an efficient tool to provide protection for workers against unemployment and foster formal job creation in developing countries. How much workers value this protection and to what extent it allows a more efficient job search are two key parameters that determine its effectiveness. However, evidence shows that important challenges remain in the introduction and expansion of unemployment insurance in developing countries. These challenges range from achieving coverage in countries with high informality, financing the scheme without further distorting the labor market, and ensuring progressive redistribution.
Keywords: J65; J46; N16; 330; unemployment insurance; informality; developing countries; labor markets; Latin America